AB0722 The impact of a referral strategy for axial spondyloarthritis in young patients with chronic low back pain: short term outcomes of the impact study. (15th June 2017) - Hoeven, L Van; Korver, A; Appels, C; Hazes, J; Hoogen, F van den; Oosterhout, M van; Oostveen, J; Spoorenberg, J; Tchetverikov, I; Kuijper, T; Koes, B; Weel, A
Abstract : Background: A substantial amount of young patients with chronic low back pain (CLBP) have axial spondyloarthritis (axSpA), but early recognition of these patients is difficult for general practitioners (GPs). Recently, the CaFaSpA referral rule has been published and externally validated. It is an easy to use referral strategy that has shown to be able to identify patients with CLBP at high risk for axSpA in a primary care setting. The CaFaSpA referral rule consists of 4 items: inflammatory back pain, family history of axSpA or related disease, good reaction to NSAIDs and duration of back pain ≥5 years. If at least 2 out of 4 items are present, the referral rule is positive and a referral to a rheumatologist is advised. Objectives: To assess the effect of the CaFaSpA referral rule on disability in young CBPP patients by comparing it with usual care, using the format of an impact analysis. Methods: A cluster randomized controlled trial with GP practices as clusters. GP practices were randomized to either the intervention (use of the referral strategy) or control (usual care) group. Within these GP practices, patients aged 18–45 years with current CLBP were recruited. The primary outcome was disability caused by low back pain, measured with the Roland Morris Disability Questionnaire (RMDQ) scale 0–24. RMDQ score was obtained at baseline and 4 months after a referral advice was made. A higher RMDQ score means more disability. For statistical analysis a linear mixed effects regression model was used. Results: 92 primary care practices were randomized, 679 patients participated (64% women, mean age 36.2 years (SD7.5) and median CLBP duration 9 years (IQR 4–15 years). 333 patients were randomized to the intervention group, both groups had similar characteristics at baseline. Sixty percent of participants had a positive referral rule. RMDQ scores are shown in table 1 . Sub scores are shown for patients with a positive outcome of the referral rule (PRR) and a negative outcome of the referral rule (NRR). The change in RMDQ score after 4 months in the intervention group was -0.74 (95% confidence interval (CI) -1.31 – -0.18) and in the control group -0.46 (95% CI -0.98 – 0.05). There was no significant difference between groups. Conclusions: Compared with usual care, use of the CaFaSpA referral rule in CLBP patients in a primary care setting did not significantly impact disability in these patients, 4 months after a referral advice was made. Results after 12 and 24 months should be awaited before definitive conclusions about the impact of the CaFaSpA referral rule for axSpA in CLBP patients can be made. Disclosure of Interest: None declared